How Spontaneous Volunteers Disrupt the Management of Forced Migrants and Life Seekers - Kjellmo Larsen, Henrik. author. aut Link
XIV, 217 p. 13 illus., 10 illus. in color.
Keywords: This book explores how spontaneous volunteers disrupt the politics and practices of managing the movement of life seekers. Drawing on rich empirical material from the 2015 Greek refugee crisis, it reveals how these unaffiliated actors challenge humanitarian systems shaped by neoliberal logic and border violence. Through a multimethod approach—including autoethnography, interviews, and participatory observation—the book traces how spontaneous volunteers expose the failures of international organisations and states to uphold human rights. It shows how their presence unsettles dominant narratives, disrupts illiberal governance, and surfaces the emotional and moral cost of crisis response. Chapters examine the criminalisation of aid, the commodification of humanitarian values, and the psychosocial toll on those who step in where institutions fall short. Situated in Critical Development Studies, this book offers interdisciplinary insights relevant to scholars, practitioners, and policymakers working on solidarity, humanitarianism, security, and global governance. Henrik Kjellmo Larsen, PhD, is a researcher and civic response consultant affiliated with Monash University and founder of Volunbridge. With over a decade of experience engaging with spontaneous volunteers, his work explores how they disrupt the management of life seekers and challenge dominant approaches to humanitarian governance.